Educator in The Prespective of Islamic and Western Education Theory - Basir, Abdul (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2020)
Educators take as an important rule in educational system. They are the ones who are responsible for the students in achieving their educational goals. Basically, there is no difference concept of educators in both Islamic and Western Education. However, Islam has broader perspectives compared to the Western one, since in Islam Allah is believed as the first and foremost teacher or educator. Then, this is continued by the Prophet Muhammad as a recipient of revelations from Allah, and then it is inherited to the Islamic Scholars and even parents to educate their followers, children, and all family members. The position of educators is highly appreciated according to Islamic Education, since the source of the knowledge taught to the human is directly from Allah the Almighty God. Therefore, the nature of educators should become role models which can be taken as a good example for the students in order to improve the quality of theit faith and piety. Thus, the terms and conditions for an educator are s/he must be an adult, has good personality and character, has broaden knowledge and skills, and also good attitudes and consistency based on Islamic taughts.